Life events as predictors of children’s behavioral/emotional problems. - Lim, Si Huan. (2009)
This study examined the contribution of life events to children’s behavioral/emotional problems. One thousand and nine clinical cases from the Child Guidance Clinic were sampled. Age, gender, and 11 life events were coded. Children’s ages ranged from 4 to 18 years. Children’s behavioral/emotional problems were measured using the Child Behavior Checklist for ages 4 – 18 (CBCL), which yielded CBCL T-scores for internalizing, externalizing, and total problems. Exploratory factor analysis yielded five categories of life events as independent variables. A series of hierarchical multiple regression analyses revealed that controlling for age and gender, life events accounted for total behavioral/emotional problems. When age and gender were controlled for, internalizing behavioral problems were accounted for by a greater number of life events.